Accounting Ethical Practices and Financial Reporting Quality by Mukwano Group of Companies. - Micheal Nsadha (Uganda Christian University, 2023)
This research aimed at the Accounting Ethical practices and financial reporting Quality by Mukwano group of companies. This study based on three main objectives which were: To examine the effects of disclosure on the Quality of financial reports of Mukwano group of companies, to examine the effects of objectivity on the quality of financial reports of Mukwano group of companies, to examine the effects of integrity on the quality of financial reports of Mukwano group of companies. The researcher used both qualitative and quantitative research designed with a sample of 52 respondents. Qualitative data was obtained through questionnaires, interviews, and observation while Quantitative data was obtained through computation and analysis. The collected data was analyzed using Microsoft Excel and presentation in the form of tables. The study findings revealed that there is a significant relationship between Accounting Ethical Practices and financial reporting quality of Mukwano group of companies. The level of significance was computed at 0.000 which indicates that the results were not by chance. The Pearson correlation coefficient was computed at 0.674 which interpreted as a fairy strong relationship. The significance level and the Pearson R coefficient led us to interpretation of a significant fairly strong positive relationship. The study recommends that Accountants should upload high positive attitudes with respect to quality financial reports, relationships that bias influenced the professional judgement of the professional accountants should be avoided. The study concludes that Mukwano group of companies needed to wait till a case was formally reported buy might cause preliminary investigation to be commenced once the general public becomes aware of such breach and this might be through the new media- printed or electronic.
This is a dissertation.